EMERGING TRENDS IN ROBOTIC SURGERY: IMPROVING PRECISION AND OUTCOMES - Dilshada Bano (PT. Radja Intercontinental Publishing, 2024)
Robotic surgery is revolutionising modern medicine, offering unprecedented precision and improved outcomes in various surgical disciplines. This article explores the emerging trends in robotic surgery, highlighting advancements in technology, integration of artificial intelligence, and innovative applications across fields such as oncology, cardiology, and orthopaedics. The shift towards minimally invasive techniques facilitated by robotic systems has reduced surgical trauma, shortened recovery times, and improved patient outcomes. Key developments, including haptic feedback systems, augmented reality for enhanced visualisation, and machine learning algorithms for pre-operative planning, are examined. The article also addresses the challenges of high costs, the need for specialised training, and ethical considerations associated with robotic systems. With continuous improvements in affordability and accessibility, robotic surgery is poised to become a cornerstone of precision medicine. The discussion underscores the transformative potential of these technologies in enhancing surgical efficiency and patient care while paving the way for future innovations.